Gone Tomorrow: Jack Reacher #13 - Child, Lee (New York : Delacorte Press, 2009)
When a young woman blows her brains out on a New York subway a few feet from Jack Reacher, he becomes understandably perturbed. His quest to find out why takes the large and lethal Clint Eastwood-like loner back to the Cold War and reveals a connection to presidential politics in this 13th Reacher novel (after Nothing to Lose), complete with cover-ups and numerous intriguing twists. The government is hiding something, and al Qaeda wants somethingbut what? All the while, goons from both sides assault and kidnap Reacher and two cops who are his companions. Reacher concludes that the Pentagon staffer who killed herself had some kind of information critical to national security. As the dead and injured pile up, the ever-resourceful and vengeful Reacher takes on nearly a score of the bad guys in an exciting climax to an enthralling book that is as satisfying as its predecessors.
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Conspiracies -- Fiction; New York (N.Y.) -- Fiction; Suspense fiction